Characterization of Cellulases of Thermopiles Bacteria from Rimbo Panti Hot Spring, West Sumatera, Indonesia - Armaini; Dharma, Abdi; Munaf, Edison; Syukur, Sumaryati; Jamsari (Asian Journal of Chemistry, 2013)
The thermopiles bacteria from hot springs Rimbo Panti, West Sumatera, Indonesia was screened. Screening is done by using a selection medium for thermopiles bacteria and to examine the potential of cellulases used medium containing carboxy methyl cellulose and stained with Congo red which marked the formation of clear zones, where the isolates obtained was 14. In this study, the effect of temperature and pH on endoglucanases activity showed that, it is thermo-tolerant enzyme because at the temperature from 50-100 ºC still show a fairly stable and increas the activity up to 100 ºC, with the tolerant of pH ranging from pH 4.8 to 7.5. The three isolates were also thermo-stable at temperatures 70 to 100 ºC. Maximum activity of exoglucanases produced by the 1M-2 isolates sample is 40.20 units/mg at 70 ºC and pH 6.5, on the other hand, the highest maximum activity of endoglucanases produced by, isolates 1M-3 is 70.50 units/mg, at optimum conditions of temperature 100 ºC and pH 7.5. Moreover, the highest maximum activity of b-glucosidases produced by, 1M-2 isolates is 65.30 units/mg at temperature 80 ºC and pH 7.5.